bahasa inggris - Firdaus, Ilham; Mukhroji; Khairuman (Jurnal Inotera, 2026)
The rapid development of information technology has encouraged improvements in public service delivery, particularly in the health sector. However, residents of Banda Aceh City still experience difficulties in accessing fast, accurate, and integrated information regarding the locations and services of health facilities. This study aims to design and develop a web-based health service information system integrated with a Geographic Information System (GIS) to support public access to health facility information and assist data management at the Aceh Health Office. The system was developed using the Waterfall model, which includes requirement analysis, system design, implementation, testing, and maintenance stages. The proposed system provides an interactive digital map displaying hospitals and community health centers (puskesmas), complete with facility details, service types, and route navigation features. System testing using the black box method indicates that all main system functionalities operate according to user requirements. The results show that the system improves accessibility to health service information and supports more efficient management of health facility data in Banda Aceh City.